A General Uniqueness Theorem concerning the Stability of Additive and Quadratic Functional Equations. (17th February 2015) - Lee, Yang-Hi; Jung, Soon-Mo
Abstract : We prove a general uniqueness theorem that can be easily applied to the (generalized) Hyers-Ulam stability of the Cauchy additive functional equation, the quadratic functional equation, and the quadratic-additive type functional equations. This uniqueness theorem can replace the repeated proofs for uniqueness of the relevant solutions of given equations while we investigate the stability of functional equations.